Skin of color representation in cosmetic clinical trials: A literature review. Issue 6 (4th April 2022) - Akintilo, Lisa; Pulavarty, Akshay; Onwudiwe, Oge; Garibyan, Lilit; Lee, Kachiu
Abstract: Despite cosmetic procedures being on the rise in the US in all demographics, cosmetic procedures remain heavily skewed towards non‐skin of color patients. Cosmetic clinical trials in the United States must be representative of the ever‐increasing diversity of the US population. We sought to analyze published cosmetic randomized controlled trials, both industry‐sponsored and investigator‐initiated, to characterize and assess representation of skin of color participants over the past three decades. Our study shows that industry sponsorship correlates with poor study participant ethnic/racial diversity in aesthetic randomized controlled trials, and should serve as a call to action for industries to increase the inclusion of skin of color participants in their studies.